Polysaccharide-based materials for cartilage tissue engineering applications - Oliveira, J. T. (2011)
Tissue engineering was proposed approximately 15 years ago as an alternative and innovative way to address tissue regeneration problems. During the development of this field, researchers have proposed a variety of ways of looking into the regeneration and engineering of tissues, using different types of materials coupled with a wide range of cells and bioactive agents. This trilogy is commonly considered the basis of a tissue-engineering strategy, meaning by this the use of a support material, cells and bioactive agents. Different researchers have been adding to these basic approaches other parameters able to improve the functionality of the tissue-engineered construct, such as specific mechanical environments and conditioned gaseous atmospheres, among others. Nowadays, tissue-engineering principles have been applied, with different degrees of success, to almost every tissue lacking efficient regeneration ability and the knowledge and intellectual property produced since then has experienced an immense growth. Materials for regenerating tissues, namely cartilage, have also been continuously increasing and most of the theoretical requirements for a tissue engineering support have been addressed by a single material or a mixture of materials. Due to their intrinsic features, polysaccharides are interesting for cartilage tissue-engineering approaches and as a result their exploitation for this purpose has been increasing. The present paper intends to provide an overview of some of the most relevant polysaccharides used in cartilage tissue-engineering research.